IMAGE AS THE MOST IMPORTANT ELEMENT OF MARKETING COMMUNICATIONS OF THE COMPANY - Alexey V. Moskaev; Elena V. Komarova (Статистика и экономика)
The article is devoted to use of image of the company in achieving its long-term competitiveness. Shown the position of image of the company in the commercial and communication activities of the company. Discussed methodological and practical issues of formation, research and development of image of the company. Proposed concrete steps for its creation and development, including in the light of new opportunities provided by Web 2.0 and user-generated content.